Research of Co/N/Er3+:Y3Al5O12/TiO2 in Sonocatalytic Degradation of Dyeing Wastewater - Wang, L.; Hao, C.S. (Asian Journal of Chemistry, 2014)
The preparation of the complex Co/N/Er3+: Y3Al5O12/TiO2 and Er3+: Y3Al5O12/TiO2 film was used sol–gel coating process. The nano powders samples of Co/N/Er3+: Y3Al5O12/TiO2 and Er3+: Y3Al5O12/TiO2 were characterized by X-ray diffraction, which appeared anatase mine peaks and the peaks of Co/N/Er3+: Y3Al5O12/TiO2 samples appeared broadened. Their SEM photos illustrated that the size of Co/N/Er3+: Y3Al5O12/TiO2 particles were smaller than Er3+: Y3Al5O12/TiO2 particles due to Co and N doped. The test of catalytic degradating dye wastewater by using Co/N/Er3+: Y3Al5O12/TiO2 or Er3+: Y3Al5O12/TiO2 were done under ultrasonic radiation. Er3+: Y3Al5O12/TiO2 sonocatalytic degradation efficiency was improved significantly because of doping Co and N.